2018
DOI: 10.3892/etm.2018.5736
|View full text |Cite
|
Sign up to set email alerts
|

Infectious mononucleosis and hepatic function

Abstract: Abnormal hepatic function is common in infectious mononucleosis (IM). However, it remains unknown why increased transferase levels are more common than bilirubin abnormalities in IM. The current study aimed to investigate these associations in the Chinese population. A total of 95 patients with IM (47 males and 48 females) were enrolled in the current study, as well as 95 healthy controls. Patients were sorted by sex. A receiver operating characteristic (ROC) curve was used to determine cut-off values for IM d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
4
12
0
2
Order By: Relevance
“…The gender ratio of patients with EBV-IM, as high as 1:1.2 in this study, was also compatible with that of previous studies, which concluded that there was no apparent gender predisposition [1,2]. On the other hand, sex differences in transaminase elevation are incompatible with findings of a previous study, which reported that transaminase elevation in patients with EBV-IM was more remarkable in males [4]. Because females are considered more susceptible to alcohol and acetaminophen [26,27], we also evaluated alcohol consumption and recent exposure to drugs such as acetaminophen.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The gender ratio of patients with EBV-IM, as high as 1:1.2 in this study, was also compatible with that of previous studies, which concluded that there was no apparent gender predisposition [1,2]. On the other hand, sex differences in transaminase elevation are incompatible with findings of a previous study, which reported that transaminase elevation in patients with EBV-IM was more remarkable in males [4]. Because females are considered more susceptible to alcohol and acetaminophen [26,27], we also evaluated alcohol consumption and recent exposure to drugs such as acetaminophen.…”
Section: Discussionsupporting
confidence: 88%
“…IM associated with EBV (EBV-IM) typically causes fever, pharyngitis, lymphadenopathy, and hepatitis in young male and female patients [1,2]. Previous studies on sex difference in patients with EBV-IM revealed higher age of onset [3] and remarkable elevation of transaminase in males [4] and a higher prevalence of persistent fatigue after onset of EBV-IM in female patients [5]. However, studies on sex difference in clinical symptoms and signs are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the EBV types (EBV1, EBV2 and EBV1/2), our results were statistically significantly correlated with the age group and AST and ALT values (p <0.005). Similar data were cited by Zhang et al (2018), who reported that ALT, AST and GGT levels were significantly increased in cases of infectious mononucleosis compared to controls, indicating that transferase levels can be used to diagnose and treat as a risk alert for the infection caused by MI [34].…”
Section: Discussionsupporting
confidence: 78%
“…Ninety-five patients with infectious mononucleosis and 95 healthy controls were analyzed for AST, ALT and GGT; alterations were elevated in patients with infectious mononucleosis compared to the controls [34].…”
Section: Discussionmentioning
confidence: 99%
“…A mononucleosis infectiosa szindróma (láz, nyaki lympha denomegalia, tonsillitis) hátterében az esetek 90%ában az EBV kóroki szerepe igazolható, ugyanakkor egyéb vírusok is okozhatnak hasonló klinikai tüneteket. EBV fertőzés során laborvizsgálattal a betegek több mint 80%ában emelkedett transzaminázértékek mutathatók ki, melyek általában 20 napon belül normalizálódnak [10,11]. Az emelkedett transzaminázértékek kifejezett periportalis lymphocytainfiltratióval, Kupffersejtaktivi tással és a májsejtek jelentős acidofildegenerációjával hozhatók összefüggésbe, a fertőzésre adott szisztémás válasz részjelenségeként [11].…”
unclassified